Epidemiological characteristics and pathogenic analysis of hand, foot, and mouth disease in Hebei province - LIU Zehao, WANG Le, CAO Yanyan, YAN Xiaotong, ZHAO Xin, LI Wenhui, GE Shengwang (Jichu yixue yu linchuang, 2024)
Objective To identify epidemiological characteristics and pathogen distribution of hand, foot, and mouth disease (HFMD) in Hebei Children′s Hospital in order to support prevention and treatment of HFMD. Methods A total of 1 698 cases throat swab samples from children diagnosed as HFMD from 2016 to 2023 were collected. Real-time PCR was used to detect the specific classification of HFMD. Statistical analysis was performed according to the year, season, age, and sex and enterovirus type of HFMD in the children. Results From 2016 to 2023, the ratio of male to female patients among the 1 698 children admitted to Hebei Children′s Hospital was 1.72∶1. Among them, the highest incidence rate in summer was 778 cases, accounting for 45.8% of all cases, followed by autumn, with a total of 614 cases, accounting for 36.2% of cases. The highest incidence was recorded in age group of 1-3 years, with a total of 1 032 cases (60.8%). The lowest incidence was 38 cases in age group ＞6 years old (2.2%); There were 988 cases of HFM (58.2%) caused by different strains of enterovirus undefined(EVU) except enterovirus 71(EV71) and coxsackievirus A16(CA16). Conclusions HFMD found in Hebei Children′s Hospital from 2016 to 2023 are mainly caused by enteroviruses except EV 71 and coxsackievirus A16. High morbidity is found in children aged 1-3 years, and summer and autumn are the main epidemic seasons. This result may facilitate and support decision making and strategy development in disease prevention and control as well as to strengthen public health resources.